Ursolic acid reduces oxidative stress injury to ameliorate experimental autoimmune myocarditis by activating Nrf2/HO-1 signaling pathway - Fu, Yanan; Liu, Tianshu; He, Shukun; Zhang, Yichan; Tan, Yuting; Bai, Ying; Shi, Jiawei; Deng, Wenhui; Qiu, Jiani; Wang, Zhen; Chen, Yihan; Jin, Qiaofeng; et al. (Frontiers in Pharmacology, 2023)
Background: Oxidative stress is crucial in experimental autoimmune myocarditis (EAM)-induced inflammatory myocardial injury. Ursolic acid (UA) is an antioxidant-enriched traditional Chinese medicine formula. The present study aimed to investigate whether UA could alleviate inflammatory cardiac injury and determine the underlying mechanisms. Methods: Six-week-old male BALB/c mice were randomly assigned to one of the three groups: Sham, EAM group, or UA intervention group (UA group) by gavage for two weeks. An EAM model was developed by subcutaneous injection of α-myosin heavy chain derived polypeptide (α-MyHC peptide) into lymph nodes on days 0 and 7. Echocardiography was used to assess cardiac function on day 21. The inflammation level in the myocardial tissue of each group was compared using hematoxylin and eosin staining (HE) of heart sections and Interleukin-6 (IL-6) immunohistochemical staining. Masson staining revealed the degree of cardiac fibrosis. Furthermore, Dihydroethidium staining, western blot, immunohistochemistry, and enzyme-linked immunosorbent assay (ELISA) were used to determine the mechanism of cardioprotective effects of UA on EAM-induced cardiac injury, and the level of IL-6, Nrf2, and HO-1. Results: In EAM mice, UA intervention significantly reduced the degree of inflammatory infiltration and myocardial fibrosis while improving cardiac function. Mechanistically, UA reduced myocardial injury by inhibiting oxidative stress (as demonstrated by a decrease of superoxide and normalization of pro- and antioxidant enzyme levels). Interestingly, UA intervention up-regulated the expression of antioxidant factors such as Nrf2 and HO-1. In vitro experiments, specific Nrf2 inhibitors reversed the antioxidant and antiapoptotic effects of ursolic acid, which further suggested that the amelioration of EAM by UA was in a Nrf2/HO-1 pathway-dependent manner. Conclusion: These findings indicate that UA is a cardioprotective traditional Chinese medicine formula that reduces EAM-induced cardiac injury by up-regulating Nrf2/HO-1 expression and suppressing oxidative stress, making it a promising therapeutic strategy for the treatment of EAM.